2019
DOI: 10.1111/ene.14073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cholinergic pathway disruption on cortical and subcortical volumes in subcortical vascular cognitive impairment

Abstract: Background and purpose The brain's cholinergic network has various interconnections with the cortical and subcortical structures. Disruption of cholinergic pathways by white matter hyperintensities (WMH) may cause pathologic changes within brain regions. Thus, WMH may represent an important pathological contributor to subcortical vascular cognitive impairment (scVCI). We aimed to investigate associations between the magnitude of WMH and volumetric changes in cortical and subcortical regions innervated by choli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…This type of deficit is a typical characteristic of AD, where it has been related to degenerative neuronal loss in the basal forebrain ( Sarter and Bruno, 2004 , Sarter and Bruno, 2002 , Sarter and Bruno, 1999 , Sarter and Bruno, 1997 ). However, a cholinergic deficit could also be caused by subcortical cerebrovascular damage to the cholinergic corticospinal pathways ( Lim et al, 2020 , Wang et al, 2009 ). Some studies have specifically shown that white matter hyperintensities could be related to the anatomical tracks of the cholinergic pathways ( Behl et al, 2007 , Shin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This type of deficit is a typical characteristic of AD, where it has been related to degenerative neuronal loss in the basal forebrain ( Sarter and Bruno, 2004 , Sarter and Bruno, 2002 , Sarter and Bruno, 1999 , Sarter and Bruno, 1997 ). However, a cholinergic deficit could also be caused by subcortical cerebrovascular damage to the cholinergic corticospinal pathways ( Lim et al, 2020 , Wang et al, 2009 ). Some studies have specifically shown that white matter hyperintensities could be related to the anatomical tracks of the cholinergic pathways ( Behl et al, 2007 , Shin et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results echo the previous study. The parietal regions and medial temporal regions have been suggested to be related to visuospatial attention and working memory ( Wang et al, 2015 ; Lim et al, 2020 ). The lower scores in the Trial-Making Test and Stroop Test of SIVD patients in the present study may demonstrate that the abnormally decreased ReHo/CBF ratios in these brain regions were correlated with deficits in these specific cognitive domains.…”
Section: Discussionmentioning
confidence: 99%
“…These results raise the question of whether tau accumulation may be differentiated from its role in AD spectrum disorders in relation to WMHs and VCI. It is possible that accumulated tau contributes to VCI either by triggering continuous neurotoxic processes and vascular damage including WMHs, or by its local cumulative effects on the interruption of the cholinergic pathway [59] in combination with the microstructural alterations of WMHs [60]. Recent findings have shown that cells in the CNS can release extracellular vesicles (EVs), which are a series of tiny double-membrane structures (20-2000 nm) with membrane-related interaction regions [61], filled with different molecular materials (including proteins, lipids, DNA, and various RNA species).…”
Section: Cerebral Aβ and Tau Burdenmentioning
confidence: 99%